Study of the Importance of ICT in the Curriculum of Primary and Secondary Education - Vats, Kunal; Singh, Barun Kr (Journal of Research in Innovative Teaching and Inclusive Learning, 2023)
Information and Communication Technology (ICT) has become a fundamental aspect of modern education, playing a critical role in enhancing the learning experience. This paper explores the integration of ICT in the curriculum of primary and secondary education, emphasizing its importance for improving educational outcomes, facilitating digital literacy, and preparing students for the digital age. A comparative analysis of data from various educational systems illustrates the impact of ICT on student engagement and achievement. The paper concludes with recommendations for effectively incorporating ICT into the curriculum.